ANALISIS PENERAPAN FLIPBOOK DI MADRASAH IBTIDAIYAH - Yunita; Faisal; Salsabila, Safana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines how flipbook media are implemented in Madrasah Ibtidaiyah (MI) classrooms. As digital learning resources become increasingly important for strengthening instructional quality in Islamic elementary schools, this study adopts a qualitative descriptive design combining a literature review with field observations conducted at three MI during the 2023/2024 academic year. Information was gathered through classroom observation, interviews with teachers and pupils, and document analysis. Findings show that using flipbook substantially improves students' motivation, understanding, and active engagement in lessons. Teachers noted that flipbook makes it easier to present both thematic and subject-specific material in a manner that is more interactive and visually appealing. The study also identifies several obstacles, such as limited digital skills among some teachers, insufficient access to devices, and inconsistent internet connectivity, although these can be addressed through adequate training and institutional backing. Overall, the findings indicate that flipbook is an effective and practical learning medium for MI, and broader adoption is recommended to enhance the quality of elementary education.